Analysis of Landslide Susceptibility in Klaten Regency - Febriana, Oryza; Saputra , Aditya (Amcolabora, 2024)
Landslide disasters are frequently occurring events in Indonesia. The northern part of Klaten Regency, situated on the slopes of Mount Merapi, and the southern part, which directly borders limestone hills, are vulnerable to landslides due to their elevated terrain. This research aims to investigate the role of Geographic Information Systems (GIS) in analyzing, mapping, and identifying areas prone to landslide disasters. Mapping landslide susceptibility as a GIS application aims to be a disaster mitigation effort, thereby minimizing the resulting impacts and losses. The mapping is conducted based on the Puslattinak method, using several parameters such as rainfall, slope, rock types, land use, and soil types. This mapping employs a weighted multi-level analysis method, where each parameter has a different weight depending on its influence on landslide disasters. The results of this research include the Landslide Susceptibility Map of Klaten Regency in 2022. According to the research findings, Klaten Regency is divided into three susceptibility classes: low (17,868.23 hectares), medium (41,494.22 hectares), and high (10,533.96 hectares), with rainfall intensity being the most influential parameter